2017
DOI: 10.3389/fendo.2017.00013
|View full text |Cite
|
Sign up to set email alerts
|

ACTH Receptor (MC2R) Specificity: What Do We Know About Underlying Molecular Mechanisms?

Abstract: Coincidentally, the release of this Research Topic in Frontiers in Endocrinology takes place 25 years after the discovery of the adrenocorticotropic hormone receptor (ACTHR) by Mountjoy and colleagues. In subsequent years, following the discovery of other types of mammalian melanocortin receptors (MCRs), ACTHR also became known as melanocortin type 2 receptor (MC2R). At present, five types of MCRs have been reported, all of which share significant sequence similarity at the amino acid level, and all of which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 221 publications
(198 reference statements)
0
48
0
1
Order By: Relevance
“…Many studies have shown that the appropriate function of MC2R is closely related to the expression of MRAP . Therefore, changes in MRAP protein were examined in VSMCs before and after ACTH stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the appropriate function of MC2R is closely related to the expression of MRAP . Therefore, changes in MRAP protein were examined in VSMCs before and after ACTH stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that MC2R is differentially affected by MRAP isoforms. MRAP‐α provides higher sensitivity to ACTH, whereas higher cAMP response and membrane trafficking occur during co‐expression with MRAP‐β . MC2R is confined to the endoplasmic reticulum and cannot localize to the cell membrane when the cell lacks MRAP .…”
Section: Introductionmentioning
confidence: 99%
“…MСR2 рецепторы действуют совместно с МС2 добавочным протеином (MRAP), который абсолютно необходим для связывания с АКТГ и передачи сигнала [44]. MRAP имеет отдельный трансмембранный домен и форму антипараллельного гомодимера, стабильно ассоциированного с МСR2 в плазматической мембране [35,44]. Для активации МСR2 рецепторов особенно важны два участка АКТГ: His-Phe-Arg-Trp (АКТГ 6-9 ) и Lys-Lys-Arg-Arg-Pro (АКТГ [16][17][18][19][20] ).…”
Section: рецепцияunclassified
“…They can activate MC1R, MC3R, MC4R, and MC5R to trigger cAMP production without much selectivity. The MC2R is a special member of MCRs that can only be activated by adrenocorticotropic hormone [13], and thus would not be affected by peptide drugs based on MSHs. NDP-α-MSH (MT-I), the first generation of peptide drug targeting the melanocortin system, was developed using α-MSH as a template.…”
Section: Introductionmentioning
confidence: 99%